Twenty years of universal vaccination against hepatitis B in Italy: achievements and challanges - Luisa Romano'; Sara Paladini; Alessandro R. Zanetti (SAGE Publishing, 2012)
Viral hepatitis B is a vaccine-preventable disease. Vaccination has proved to be safe and highly effective in reducing the incidence, the carrier rate and HBV-related mortality on a global scale. In Italy, universal vaccination against hepatitis B started in 1991 in infants as well as in adolescents, providing an outstanding record of safety and effectiveness. Within a few years, over 95% coverage was consistently reported. Today, some 17 million people are immune against hepatitis B and their immunity has been shown to be long-lasting. At present, no booster is required in healthy vaccinated people to sustain protection. Surveillance data from Italy have shown a clear overall decline in hepatitis B among successfully vaccinated individuals. Furthermore, a generation of children and young people (at present cohorts ranging from 0 to 32 years) is emerging with practically no markers of HBV infection. Italy's vaccination programme has resulted in substantial progress being made towards the prevention and control of hepatitis B. The vaccination programme must continue. Maintaining mandatory vaccination of infants and increasing HBV vaccination coverage in high-risk groups, including households of HBsAg carriers as well as immigrants, remain a priority for the future.